Adipose tissue-derived microvascular fragments promote lymphangiogenesis in a murine lymphedema model. (July 2022) - Frueh, Florian S; Gassert, Laura; Scheuer, Claudia; Müller, Andreas; Fries, Peter; Boewe, Anne S; Ampofo, Emmanuel; Rübe, Claudia E; Menger, Michael D; Laschke, Matthias W
Chronic lymphedema after cancer treatment is common and there is still no cure for this disease. We herein investigated the lymphangiogenic capacity of adipose tissue-derived microvascular fragments (MVF), which contain stem cells and lymphatic vessel fragments. Secondary lymphedema was induced in the hindlimbs of C57BL/6J mice. Green fluorescence protein (GFP) + MVF were isolated from transgenic C57BL/6Tg (CAG-EGFP)1Osb/J mice, suspended in collagen hydrogel, and injected in the lymphadenectomy defect of wild-type animals. This crossover model allowed the detection of MVF-derived blood and lymphatic vessels after transplantation. The MVF group was compared with animals receiving collagen hydrogel only or a sham intervention. Lymphangiogenic effects were analyzed using volumetry, magnetic resonance (MR) lymphography, histology, and immunohistochemistry. MVF injection resulted in reduced hindlimb volumes when compared to non-treated controls. MR lymphography revealed lymphatic regeneration with reduced dermal backflow after MVF treatment. Finally, MVF transplantation promoted popliteal angiogenesis and lymphangiogenesis associated with a significantly increased microvessel and lymphatic vessel density. These findings indicate that MVF transplantation represents a promising approach to induce therapeutic lymphangiogenesis.